Exercise deprivation increases negative mood in exercise-addicted subjects and modifies their biochemical markers - Antunes, Hanna Karen Moreira; Leite, Geovana Silva Fogaça; Lee, Kil Sun; Barreto, Amaury Tavares; Santos, Ronaldo Vagner Thomatieli dos; Souza, Helton de Sá; Tufik, Sergio; de Mello, Marco Tulio (Physiology & behavior, 2016)
The aim of this study was to identify the possible association between biochemical markers of exercise addiction and affective parameters in a sample of athletes during 2weeks of withdrawal exercise. Eighteen male runners were distributed into a control group (n=10) composed of runners without exercise addiction symptoms and an exercise addiction group (n=8) composed of runners with exercise addiction symptoms. The volunteers performed a baseline evaluation that included affective questionnaires, blood samples, body composition and an aerobic test performed at ventilatory threshold I. After the baseline evaluation, the groups started an exercise withdrawal period that was sustained for 2weeks. During exercise withdrawal, an actigraph accelerometer was used to monitor the movement index, and CK and LDH were measured in blood samples to validate the non-exercise practice. At the end of the exercise withdrawal period, a blood collection, aerobic test and mood scale was performed in the re-test. The results showed that at the end of the experimental protocol, when compared with the control group, the exercise addiction group showed an increase in depression, confusion, anger, fatigue and decreased vigor mood that improved post-exercise, along with low levels of anandamide at all time-points evaluated and a modest increase in β-endorphin post-exercise. Moreover, the exercise addiction group showed a decrease in oxygen consumption and respiratory exchange ratio after the exercise withdrawal period, which characterized a detraining phenomenon. Our data suggest that a 2-week withdrawal exercise period resulted in an increase of negative mood in exercise addiction; additionally, exercise addiction showed low levels of anandamide. •An exercise-withdrawal period resulted in an increase in negative mood.•Exercise addicted athletes showed lower levels of anandamide.•Anandamide levels did not increase post-exercise in exercise-addicted athletes.•Individuals with exercise addiction may have a dysfunctional endocannabinoid system.